Inovasi Layanan Aplikasi e-Samsat Dalam Pembayaran Pajak Kendaraan Bermotor Di Provinsi Riau - Evi Zubaidah; Lubis, Ema Fitri (Jurnal Niara, 2021)
With the number of tax payment services at the Samsat office in Riau province, the community needs service innovation that is easier to access payment services for motorized vehicle taxes.So that the E-samsat service application emerged ,which is an online application that aims to serve and facilitate the public in paying motorized vehicle taxes.The purpose of this study is to describe in depth the innovation of the E-Samsat application service in the payment of motor vehicle tax in Riau Province as a form of excellent service at the E-Samsat office of Riau Province.This study uses the theory of Everett M.Rogers(2003) in Suwarno (2008:17). In its application,innovation has attributes inherent in the innovation.The innovation attributes referred to are as follows : Relative Advantage, Compatibility, Complexity,Triability (possibility to be tried),Observability (easily observed).The research method used in this research is descriptive method qualitative data collection techniques through interviews, observation and documentation. Data collection, data reduction, and drawing conclusions made on data analysis techniques.The results of this study indicate that the Relative Advantage is the easiness of the community in handling motorized vehicle tax payments (PKB).Compatibility (suitability) where the E-Samsat service innovation for the people of Pekanbaru city is in accordance with the current conditions of technological development. Complexity in which the innovation of E-Samsat services is not considered complicated in the implementation process.Then Triability (possibly tested) the people of Pekanbaru City who responded positively to the existence of E-Samsat service. Furthermore from Observability (ease of observation) with fairly simple service procedures electronically. Keywords : Innovation, Service, E- Samsat Riau Province